Photosensitizer IR700DX-6T- and IR700DX-mbc94-mediated photodynamic therapy markedly elicits anticancer immune responses during treatment of pancreatic cancer. (October 2021) - Zhang, Dawei; Xie, Qing; Liu, Yang; Li, Zongyan; Li, Haiyan; Li, Shiying; Li, Zhen; Cui, Jing; Su, Meng; Jiang, Xiaofeng; Xue, Ping; Bai, Mingfeng
Abstract: Background/Aims: IR700DX-6T and IR700DX-mbc94 are two chemically synthesized photosensitizers (PSs) that target the translocator protein (TSPO) and type 2 cannabinoid receptor (CB2 R), respectively, for photodynamic therapy (PDT) of cancer. Recently, we found that IR700DX-6T and IR700DX-mbc94 exhibited high selectivity and efficiency in PDT for breast cancer and malignant astrocytoma. Yet, the phototherapeutic effects of the PSs on pancreatic cancer and underlying mechanisms remain unknown. This study investigated the effect of IR700DX-6T- or IR700DX-mbc94-PDT on pancreatic cancer and whether the treatment involves eliciting anticancer immune responses in support of superior therapeutic efficacy. Methods: Four pancreatic cancer cell lines were used for in vitro studies. C57BL/6 mice bearing pancreatic cancer cell-derived xenografts were generated for in vivo studies regarding the therapeutic effects of IR700DX-6T-PDT and IR700DX-mbc94-PDT on pancreatic cancer. The immunostimulatory or immunosuppressive effects of IR700DX-6T-PDT and IR700DX-mbc94-PDT were examined by detecting CD8 + T cells, regulatory T cells (Tregs ), and dendritic cells (DCs) using flow cytometry and immunohistochemistry (IHC). Results: TSPO and CB2 R were markedly upregulated in pancreatic cancer cells and tissues. Both IR700DX-6T-PDT and IR700DX-mbc94-PDT significantly inhibited pancreatic cancer cell growth in a dose- and time-dependent manner. Notably, assessment of anticancer immune responses revealed that both IR700DX-6T-PDT and IR700DX-mbc94-PDT significantly induced CD8 + T cells, promoted maturation of DCs, and suppressed Tregs, with stronger effects exerted by IR700DX-6T-PDT compared to IR700DX-mbc94-PDT. Conclusions: IR700DX-6T-PDT and IR700DX-mbc94-PDT involves eliciting anticancer immune responses. Our study has also implicated that PDT in combination with immunotherapy holds promise to improve therapeutic efficacy for patients with pancreatic cancer. Graphical Abstract: ga1